148 Developing an enhanced supportive care service for women suffering from the adverse effects of cancer and its treatment. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Taroni, Katie; Reeves, Helen; Hill, Katherine
Abstract : The effects of cancer and its treatment can have major adverse effects on the women it has affected and their families. This service has been set up with the support of Sutton Breast Friends and St Giles Hospice and will enable patients to discuss issues which were previously unrecognised relating to the impact on their altered body image, well-being and sexuality in a comfortable and open environment with a specialist nurse who has the skills to empower these patients to live their lives well, when suffering from the adverse effects of cancer and its treatment. Focus groups were utilised at the start to ensure that the service was set up how women wanted to ensure its success. By developing this service and delivering this model of care, our aim is to: improve the wellbeing of women suffering with cancer and the adverse effects of its treatment enable women to take control and manage a range of problems impacting on their body image, sexuality and wellbeing enable wives/husbands/partners to discuss the issues and concerns relating to how cancer and its treatment may impact on their relationship prevent relationship disconnect linked to cancer and its treatments There will continue to be an unmet need and these issues will remain unresolved for patients affecting their quality of life, and their ability to reconnect with their relationships. Evidence shows increased risk of relationship breakdown when suffering from the adverse effects of cancer and its treatment. Due to this being a new service outcome measures will be collected and will be used to demonstrate the effect the intervention has had on patients self-worth, confidence and state of mind.